1998
DOI: 10.1016/s0014-5793(98)00258-0
|View full text |Cite
|
Sign up to set email alerts
|

Vanadate fully stimulates insulin receptor substrate‐1 associated phosphatidyl inositol 3‐kinase activity in adipocytes from young and old rats

Abstract: Vanadate stimulates adipocyte 2-deoxyglucose transport and GLUT-4 translocation to the membrane through an insulin receptor-independent but wortmannin-inhibitable pathway. Vanadate stimulates PI 3-kinase in anti-IRS-1 immunoprecipitates and the binding between IRS-1 and the p85K K subunit of PI 3-kinase. In insulin-resistant adipocytes from old rats vanadate fully stimulates IRS-1-associated PI 3-kinase, but partially activates glucose uptake. We conclude that : (a) vanadate stimulates 2-deoxyglucose uptake us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…However, there is a marked impairment of both IR autophosphorylation and its intrinsic tyrosine kinase activity during aging (Ruiz et al 1992). Moreover, in isolated adipocytes from old rats we have also shown that insulin stimulation of IRS-1-associated PI3K, glucose uptake and glucose transporter 4 (GLUT4) translocation to the plasma membrane is reduced (Molero et al 1998).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, there is a marked impairment of both IR autophosphorylation and its intrinsic tyrosine kinase activity during aging (Ruiz et al 1992). Moreover, in isolated adipocytes from old rats we have also shown that insulin stimulation of IRS-1-associated PI3K, glucose uptake and glucose transporter 4 (GLUT4) translocation to the plasma membrane is reduced (Molero et al 1998).…”
Section: Introductionmentioning
confidence: 77%
“…We have previously shown that insulin-resistant adipocytes from old rats are characterized by decreased IR autophosphorylation and by impaired insulin stimulation of IRS-1-associated PI3K activity, GLUT4 translocation to the plasma membrane, glucose uptake and MAPK activity (Carrascosa et al 1989, Molero et al 1998. These data can partially be explained with the results presented here because insulin signaling is dependent on IR and IRS activation, and we show that aging down-regulates the expression of IR-B (the isoform considered to transmit the insulin signal more efficiently).…”
Section: Effect Of Aging On Ir and Irs Protein Expression In Isolatedmentioning
confidence: 99%
“…Consequently, glucose-uptake is related to the inhibition of FFA-release from isolated rat adipocytes treated with epinephrine. 28,29,48) Vanadium compounds are considered to activate IRS, 49) PI3-K, 50) GLUT-4, 51,52) cyclic nucleotide phosphodiesterases (PDEs), 53) and protein tyrosine phosphatases (PTPs), 54,55) analogous with the action of insulin. While, vanadyl ions inhibit FFA-release from adipocytes treated with epinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…[57][58][59][60] Vanadium at 1 mM has been found to stimulate the IRS-1 associated with PI3-K activity and GLUT-4 translocation without activating the insulin receptor in rats. 49) In these previous reports, it was considered that glucose-uptake into the cell by vanadium compounds was stimulated without activating the insulin receptor. Such poor evidence for the contribution of vanadium compounds to the insulin receptor suggests the concentration-dependent affinity of vanadium compounds for intracellular enzymes and substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Following the treatment, cells were incubated in the absence or presence of 16 nmol/l porcine insulin or 1 mmol/l Na 3 VO 4 (Sigma). After 5 min, the medium was aspirated, cells were washed in PBS, lysed in homogenization buffer, and centrifuged at 8,000g for 30 min as previously described (34,35). Infranatants (cytosolic extracts) were used for determination of mitogen-activated protein kinase (MAPK) activity and glycogen synthase kinase (GSK)3 phosphorylation.…”
Section: Isolation and Fractionation Of Adipocytes For In Vitro Expermentioning
confidence: 99%